Change of Eyelid Parameters in Patients With Marin-Amat Syndrome. Issue 3 (May 2020) - Chao, Yu-Jang; Tsai, Chieh-Chih; Huang, Yu-Yun; Lin, Che-Yu; Yu, Wei-Kuang; Kau, Hui-Chuan; Liu, Catherine Jui-Ling
Abstract : Purpose: Marin-Amat syndrome is an acquired facial synkinesis manifesting as involuntary eyelid closure on jaw movement. The authors investigate the clinical features, especially the quantitative changes in eyelid parameters of patients with Marin-Amat syndrome. Methods: Patients with Marin-Amat syndrome between 2015 and 2017 in a medical center were collected. Clinical features and the change of eyelid parameters, including margin reflex distance 1 (MRD-1), margin reflex distance 2 (MRD-2), and palpebral fissure height, were evaluated. Results: There were 5 men and 3 women with a mean age of 76 years. All had a history of facial palsy. The mean time to onset of Marin-Amat syndrome was 4.4 years after facial palsy. Seven patients (87.5%) developed subsequent ipsilateral facial spasm after facial palsy. Most patient complaints were ptosis (62.5%) and ptosis on eating (37.5%). The mean palpebral fissure height of involved eyes decreased from 5.88 to 2 mm on jaw opening ( p = 0.011), which resulted from decrease in MRD-1 (from 2.06 to 0.06 mm, p = 0.012) and MRD-2 (from 3.81 to 1.94 mm; p = 0.012). Botulinum toxin A (Botox) injection into the periorbital orbicularis muscle in 6 patients significantly relieved the change of palpebral fissure height on jaw opening compared with that before injection (9.9% vs. 68.6 %, p = 0.027). Conclusions: Most patients with Marin-Amat syndrome present with ptosis and might be overlooked or underestimated. The reduction in palpebral fissure height in our patients with Marin-Amat syndrome was due to involuntary orbicularis oculi muscle contraction, resulting in decrease of both the MRD-1 and MRD-2 on jaw opening. Abstract : To evaluate the changes in eyelid parameters of patients with Marin-Amat syndrome can help to understand this underestimated disease.